CLASSIFICATION OF POETIC SERIES RELATED TO TRAVEL IMPRESSIONS (On the example of Tajik and Uzbek poetry of the period of national renaissance) (Scientific journal of the Fergana State University, 2024)
The article analyzes the lyrical works of national renaissance poet Ahmad Donish and son of Zakirjon Kholmuhammad Furqat, who were born as a result of their travels to Europe. At the same time, the realities of the written epic written by the poet son of Mulla Hashim Hayratiyr from Shahri Khan were classified, and the characteristics of the Western national culture and the different aspects of the works of these poets were identified.